Wpływ władz państwowych na obsadę stanowisk kościelnych w Diecezji Łomżyńskiej w latach 1945-1989 - Jemielity, Witold (Prawo Kanoniczne, 2006)
Immediately after the Second World War the Bishop appointed Parish-Priests on the base of the concordat regulations issued in the year 1925, while, on the other hand, he appointed curates by himself. On motion of the decree issued on this February 9th in the year 1953 filling up vacancies for both Parish-Priests and Curates was completely dependent on the will of the government The decree issued on this December 31st in the year 1956 and binding till the year 1989 refered to Parish-Priests only. In the 60's the voivodship authorities repeatedly rejected Bishop's applications so he refered the matter to the ministry. The main reason of the State authorities' denial was defianse of the priests as regards registration of the catechetic points and keeping stock-books. Since the 70's government authorities less and less resticted the power of the Bishop as regards filling up church vacancies and since 1989 the Bishop has gained complete freedom on this matter.